2011
DOI: 10.1142/s1084946711001872
|View full text |Cite
|
Sign up to set email alerts
|

Through a Fractured Lens: Women Entrepreneurs and the Private Equity Negotiation Process

Abstract: Access to financial resources remains an important aspect of new venture start-up and growth strategies. While women still obtain a small amount of total private equity investment, they are increasingly involved in developing high growth ventures which may be attractive investment opportunities for venture capitalists and business angels. Contract, or term sheet, negotiation is an important stage of the investment process. Although gender-related differences in negotiation styles are well documented in other f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…A total of three papers develop theoretical models explaining the interaction between entrepreneurs, BAs and VCs in the funding process (Fairchild, 2011;Conti et al, 2013;Hellman and Thiele, 2015). Finally, only a few papers explore the negotiation phase, focusing on how BAs' contracts affect their involvement in invested firms and investments through syndicates (Kelly and Hay, 2003), in comparison with VCs' contractual provisions (Ibrahim, 2008), and on the challenges faced by entrepreneurs in closing deals with BAs (Amatucci and Swartz, 2011;Douglas et al, 2014). Figure 2 summarizes the main BAs' selection criteria identified in the literature.…”
Section: Selection Evaluation and Fundingmentioning
confidence: 99%
“…A total of three papers develop theoretical models explaining the interaction between entrepreneurs, BAs and VCs in the funding process (Fairchild, 2011;Conti et al, 2013;Hellman and Thiele, 2015). Finally, only a few papers explore the negotiation phase, focusing on how BAs' contracts affect their involvement in invested firms and investments through syndicates (Kelly and Hay, 2003), in comparison with VCs' contractual provisions (Ibrahim, 2008), and on the challenges faced by entrepreneurs in closing deals with BAs (Amatucci and Swartz, 2011;Douglas et al, 2014). Figure 2 summarizes the main BAs' selection criteria identified in the literature.…”
Section: Selection Evaluation and Fundingmentioning
confidence: 99%
“…The existence of gender differences in a wide range of entrepreneurial contexts, including business ownership, growth and performance, access to finance, networking, is widely accepted, although individual studies vary in the extent of the differences identified (Cabrera and Mauricio, 2017; Loza, 2011; Marlow and McAdam, 2013; Yadav and Unni, 2016). Specifically, a number of studies have highlighted the underrepresentation of women in the population of business angel investors, have identified the recent growth in the number of women angels and have profiled some aspects of their characteristics and behaviour (Amatucci, 2016; Amatucci and Swartz, 2011; Becker-Blease and Sohl, 2007, 2011; Coleman and Robb, 2017, 2018; Gavara and Zarco, 2015; Harrison and Mason, 2007; Sohl and Hill, 2007). While there appear to be differences between women and men investors, these are neither systematic nor consistent, and an early analysis that suggested that there was more heterogeneity within the women angel population than between women and men angels (Harrison and Mason, 2007) remains largely unchallenged.…”
Section: Introductionmentioning
confidence: 99%
“…After information about desired resources has been processed, there are costs to entrepreneurs of constructing contracts to obtain these resources (Yang et al, 2012). For instance, if an entrepreneur determines that a prospective investor is a fit, the entrepreneur has additional costs (e.g., bargaining, legal fees) associated with constructing a contract outlining the key points in the transaction and the terms of the investment (e.g., the investment amount, the equity exchanged, the possibility for follow-on investment; Amatucci & Swartz, 2011). Some transactions, such as entering a lease agreement, involve creating a formal, typically written, contract between two parties.…”
Section: Entrepreneurial Ecosystem Coordination and Negotiation Costsmentioning
confidence: 99%